Urgensi Profile Pelajar Pancasila Terhadap Siswa Sekolah Dasar - Thohiroh, Nazila Syifa (Jurnal Bina Ilmu Cendekia, 2024)
Pancasila as the foundational philosophy of Indonesia has values that are relevant and can shape the character of a good student. This article explains the values of Pancasila such as Belief in the One and Only God, Just and Civilized Humanity, the Unity of Indonesia, Democracy Led by Wisdom of Deliberations among Representatives, and Social Justice for all Indonesians, in language that is easy for elementary school students to understand. Previous research has shown that the application of Pancasila values in the daily lives of elementary school students has significant benefits, such as strengthening a sense of nationality, shaping good character, fostering an attitude of tolerance, increasing harmony between individuals, and developing social awareness. However, if elementary school students do not understand and apply the values of Pancasila, they may experience obstacles in character development, loss of national identity, lack of tolerance, and lack of social awareness. Therefore, it is important for elementary school students to be introduced to and internalize the values of Pancasila through education and practical experience in the school environment, as well as to understand, internalize, and apply the values of Pancasila in their daily lives.